COMO É NASCER, VIVER E MORRER EM BETIM/MG SEGUNDO O DATASUS - Anjos, Alyne Barbosa; Brandão, Amanda Andrade; Guedes, Bianca Lopes; Lana, Diana Débora Pereira de; Souza, Luisa Paula de Almeida; Felisberto, Juliana Mara (Sinapse Múltipla, 2020)